Factors Influencing Fourth-Year Pharmacy Students’ Decisions to Pursue a Hospital Pharmacy Residency - Dupuis, Sébastien (Can J Hosp Pharm, 2016)
BACKGROUND: The Canadian Society of Hospital Pharmacists promotes the recruitment of residency-trained pharmacists for work in hospitals and related health care settings. However, Quebec hospitals are still hiring non–residency trained pharmacists, in part because of a severe shortage of hospital pharmacists. To date, no studies have examined the factors influencing the career choices of fourth-year pharmacy students in Canada. OBJECTIVES: To identify motivating factors and barriers influencing students’ decision to pursue a hospital pharmacy residency. METHODS: All 186 fourth-year students in the Faculty of Pharmacy, Université de Montréal, were invited by e-mail to participate in a validated and institutionally approved survey that was available online between March and May 2014. RESULTS: Of the 138 respondents who returned a completed survey (74% response rate), 36 (26%) planned to apply for a hospital pharmacy residency. Those planning to apply for a residency were older (p = 0.037) and had more hospital work experience (36% versus 3%, p < 0.001) than those not planning to apply. The most important motivators for pursuing a residency were potential gains in knowledge (reported by 88% of respondents, whether or not they were planning to pursue a residency), experience (80%), and self-confidence (62%). The most frequently reported barriers were recognition that a hospital pharmacy residency is a highly demanding program (65%), having work available upon graduation from the undergraduate program (43%), and financial obligations (34%). Hospital experiential rotations influenced, either positively or negatively, 23 (72%) of the 32 students who changed their decision to pursue or not pursue residency training over the course of their studies. CONCLUSIONS: The potential gain in knowledge and experience acquired through residency, the fact that it is considered a highly demanding program, and having work available upon graduation from undergraduate studies were the most influential factors in fourth-year pharmacy students’ decision of whether to pursue a hospital pharmacy residency.